Solution:
Let L represent the side length of the original square.
Note that:
1. Square root both sides:
- (L + 6)² = 9 x L²
- => √(L + 6)² = √9 x L²
2. Simplify the RHS:
- => L + 6 = 3 x L
- => L + 6 = 3L
3. Subtract L from each side.
4. Divide 2 both sides.
Double check:
- Area of square with 3 inches as side length: 3² = 9 in²
- Area of square with 9 inches as side length: 9² = 81 in²
=> 81 ÷ 9 = 9 (True)
This shows that the area of the original square is 9 times smaller than the increased square.